2018
DOI: 10.35654/ijnhs.v1i1.11
|View full text |Cite
|
Sign up to set email alerts
|

SWOT Analysis of Nursing Clinic Professional Career Ladder System (SJKP2K) in Military Hospital Jakarta

Abstract: Nursing managers must have a strong directing function towards the Professional Clinic Nurse Career Ladder System (SJKP2K). This is to improve the quality of nursing care that will be provided by nurses to patients. The military hospital in Jakarta already has the standard of planning, guidelines and SOP regarding the SJKP2K, but based on the authors' observations for two weeks in one of the rooms in the hospital, the results show that the SJKP2K implementation is not optimal. This problem then analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The main requirements for working abroad is minimum to be a diploma or bachelor's degree, having a minimum of two or three years of work experience, possessing a Registration Certificate (STR), passing an interview/written test, and medical checkup [33]. In the SWOT analysis, what is included in the Strengths category are human resources, infrastructure, training, support, and technology (hardware and software) [34]. As the fourth largest country in terms of population, Indonesia has a large number of human resources in healthcare [35].…”
Section: A Strengthsmentioning
confidence: 99%
“…The main requirements for working abroad is minimum to be a diploma or bachelor's degree, having a minimum of two or three years of work experience, possessing a Registration Certificate (STR), passing an interview/written test, and medical checkup [33]. In the SWOT analysis, what is included in the Strengths category are human resources, infrastructure, training, support, and technology (hardware and software) [34]. As the fourth largest country in terms of population, Indonesia has a large number of human resources in healthcare [35].…”
Section: A Strengthsmentioning
confidence: 99%
“…The results of the study by Pertiwi et al (2018) showed that 72% of PK I nurses exercised authority over the interventions carried out by PK I to PK IV. However, some actions are still carried out outside of their clinical assignments: 7% are the clinical authority of PK II, namely the provision of analgesics and antipyretics; 20% are clinical assignments for PK III, such as giving mask oxygen and NGT installation; and 1% is the clinical authority of PK IV.…”
Section: Introductionmentioning
confidence: 99%